1987
DOI: 10.1073/pnas.84.14.4954
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular studies on a recombinant human X chromosome: implications for the spreading of X chromosome inactivation.

Abstract: A pericentric inversion of a human X chromosome and a recombinant X chromosome [rec(X)] derived from crossing-over within the inversion was identified in a family. The rec(X) had a duplication of the segment Xq26.3--Xqter and a deletion of Xp22.3-,Xpter and was interpreted to be Xqter--Xq26.3::Xp22.3--Xqter. To characterize the rec(X) chromosome, dosage blots were done on genomic DNA from carriers of this rearranged X chromosome using a number of X chromosome probes. Results showed that anonymous sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 36 publications
(31 reference statements)
4
30
1
Order By: Relevance
“…The paternally derived Pgk-1 gene is preferentially inactivated along with all other X-linked genes in extraembryonic tissues of female embryos; however, the paternally derived Pgk-lac2 transgene was expressed in extra-embryonic tissues of all transgenic embryos, suggesting that the transgene does not carry sequences that can be imprinted to mediate paternal-specific inactivation. These results are consistent with studies of X-autosome translocations (Rastan, 1983;Mohandas et al, 1987) that suggest that inactivation of a n X-linked gene requires that it be linked to the region of the X chromosome from which inactivation is thought to be initiated.…”
Section: Discussionsupporting
confidence: 91%
“…The paternally derived Pgk-1 gene is preferentially inactivated along with all other X-linked genes in extraembryonic tissues of female embryos; however, the paternally derived Pgk-lac2 transgene was expressed in extra-embryonic tissues of all transgenic embryos, suggesting that the transgene does not carry sequences that can be imprinted to mediate paternal-specific inactivation. These results are consistent with studies of X-autosome translocations (Rastan, 1983;Mohandas et al, 1987) that suggest that inactivation of a n X-linked gene requires that it be linked to the region of the X chromosome from which inactivation is thought to be initiated.…”
Section: Discussionsupporting
confidence: 91%
“…These cases are presumed to be the result of either a recombination event in a parent carrying a pericentric inversion [23][24][25][26][27] or inherited from a phenotypically normal mother carrying the abnormal X. 28 We report two additional cases in which an Xq duplication encompassing MECP2 was accompanied by an Xp deletion, resulting from a specific intrachromosomal rearrangement in which the duplicated segment of Xq was translocated to the Xp22.3 band.…”
Section: Xp-xq Rearrangementsmentioning
confidence: 99%
“…The pregnancy was complicated by influenza associated with dehydration. Literature (n¼5) [21][22][23] Literature (n¼8) [25][26][27][28] …”
Section: Casementioning
confidence: 99%
“…Analysis of expression of X-linked markers in somatic cell hybrids that retained the rearranged X in its inactive state revealed that MIC2 and STS were expressed. G6PD, however, was not expressed, presumably as a consequence of normal inactivation of both copies of the gene (38). The observation that X chromosome material can be inactivated on both sides of a segment that is active is compelling evidence that differences in gene or chromosome organization necessary for escape from inactivation must exist.…”
mentioning
confidence: 82%
“…It is possible that some intrinsic difference in gene organization accounts for escape of MIC2 from X-inactivation. Mohandas et al (38) described a rearranged X chromosome in which a duplicated segment Xq26.3-Xqter is distal to MIC2 and STS on the tip of the chromosome short arm. The duplicated material includes G6PD locus.…”
mentioning
confidence: 99%